INNOVATIVE LEARNING STRATEGIES THROUGH EMOTIONAL APPROACHES ENHANCE THE LEARNING INTEREST OF SDN BALEDONO 2 STUDENTS - Al Insan Assalamfida, Muhammad; Kenji Ahsan, Ava; Bachrul Hilmi, Sectio; Susilo, Joko (Antis-publisher, 2025)
Objective: This study aims to explore and analyze the effectiveness of innovative learning strategies integrated with an emotional approach in enhancing elementary school students' interest in learning at SDN Baledono 2. Method: A qualitative research method with a descriptive approach was employed to assess the implementation of the Community Service Program by students from Muhammadiyah University of Sidoarjo. Data collection was conducted through observation, interviews, and documentation analysis to examine the impact of these strategies on student engagement. Results: The findings indicate a notable increase in students' enthusiasm for learning following the implementation of interactive and emotionally engaging teaching methods. The structured learning interventions successfully fostered a more dynamic and student-centered classroom environment, leading to improved participation and motivation. Novelty: This study highlights the integration of emotional engagement within innovative pedagogy as a key factor in revitalizing student interest in learning. The insights gained provide valuable recommendations for educators and future community service programs to enhance the quality of elementary education through emotionally responsive teaching strategies. Future research should explore scalable models for implementing similar approaches in diverse educational settings to ensure broader applicability and long-term impact.